Spectral Amplitude Coding Optical CDMA: Performance Analysis on Free Space Optical Channel - A. Memon, Kehkashan; W. Umrani, A.; A. Unar, M.; Shah, Wajiha; S. Chowdhry, B. (International Journal of Engineering and Technology, 2018)
In this paper, we investigate the performance of Spectral Amplitude Coding Optical Code Division Multiple Access technique based on Free Space Optical channel. SAC OCDMA is one of the most popular multiplexing techniques since many years and FSO is gaining popularity and is very useful especially in point to point communication. The system presented in this paper utilizes Walsh Hadamard code as signature code. The coder and decoder structures are based on optical filters of fiber Bragg gratings (FBGs). This system focuses on the performance analysis of FSO based systems for subtropical regions. This paper demonstrates the error rate performance in the form of eye diagrams/BER under varying channel gain and link distances. Five cases have been taken which shows that SAC OCDMA FSO system is reliable even for distances sufficient to overcome the last mile problem.Â Â